Accelerating Knowledge Discovery through Community Data Sharing and Integration - Yip, Y.L.; Section Editor for the IMIA Yearbook Section on Bioinformatics; Swiss-Prot group, Swiss Institute of Bioinformatics, Geneva, Switzerland (Yearbook of Medical Informatics, 2009)
Objectives To summarize current excellent research in the field of bioinformatics.Method Synopsis of the articles selected for the IMIA Yearbook 2009.Results The selection process for this yearbook’s section on Bioinformatics results in six excellent articles highlighting several important trends First, it can be noted that Semantic Web technology continues to play an important role in heterogeneous data integration. Novel applications also put more emphasis on its ability to make logical inferences leading to new insights and discoveries.Second, translational research, due to its complex nature, increasingly relies on collective intelligence made available through the adoption of community-defined protocols or software architectures for secure data annotation, sharing and analysis. Advances in systems biology, bio-ontologies and text-ming can also be noted.Conclusions Current biomedical research gradually evolves towards an environment characterized by intensive collaboration and more sophisticated knowledge processing activities. Enabling technologies, either Semantic Web or other solutions, are expected to play an increasingly important role in generating new knowledge in the foreseeable future.
Keywords: Medical informatics; International Medical Informatics Association; yearbook; bioinformatics; translational research; knowledge discovery